Parallel texts from the Swedish Competition Agency - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Texts collected from the Swedish Competition Authority's website around March 2018. The texts are yearly reviews and other public information from this authority.

Parallel texts downloaded from the agency's website.
What was downloaded were pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Texter insamlade från Konkurrensverkets webbplats kring mars 2018. Texterna är årsredovisningar och annan offentlig information från myndigheten.

Parallella texter nedladdade från Konkurrensverkets webbplats.
Det som nedladdades var pdf-filer. De txt-filer som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Parallella texter från Konkurrensverket
Keywords: public administration; offentlig förvaltning; economic competition; ekonomisk konkurrens; ECONOMICS; EKONOMI; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Economics; Nationalekonomi; Business Administration; Företagsekonomi; Languages and Literature; Språk och litteratur; Other Legal Research; Annan rättsvetenskaplig forskning